Ship-based Trackline Geophysical Data (MGD77) from the Drake Passage acquired during the Nathaniel B. Palmer expedition NBP1105 (2011) (IEDA: Marine-Geo Digital Library, 2012)
This data set was acquired with a ship-based Gravimeter and Subbottom Profiler during Nathaniel B. Palmer expedition NBP1105 conducted in 2011 (Chief Scientist: Dr. Nerida Wilson). These data files are of MGD77 format and include Bathymetry, Gravity (Field and Free Air Anomaly) data that were processed during the cruise